2007
DOI: 10.3141/2009-12
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Safety and Safe Routes to Schools

Abstract: Safe Routes to Schools programs are an increasingly popular means of addressing parental concerns about traffic safety and encouraging parents to permit their children to walk and bicycle to school. While there has been a good deal of recent research examining the health and physical activity benefits associated with these programs, there has been little systematic examination of the effects these programs may have on the actual safety of child pedestrians. This paper summarizes the existing empirical evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Signs, flashers, and roadway markings have all been implemented. While some studies have shown a positive effect from utilizing signs on reducing speed (Schrader, 1999;Aggarwal and Mortensen, 1993;Hawkins, 1993), others argue that signs have no effect on driver compliance with posted speed limits (Simpson, 2008;Burritt et al, 1990), leading to a lack of conclusive evidence on the value of school zone signage (Dumbaugh and Frank, 2007;Lee and Bullock, 2003).…”
Section: Driver Speed Compliancementioning
confidence: 96%
See 1 more Smart Citation
“…Signs, flashers, and roadway markings have all been implemented. While some studies have shown a positive effect from utilizing signs on reducing speed (Schrader, 1999;Aggarwal and Mortensen, 1993;Hawkins, 1993), others argue that signs have no effect on driver compliance with posted speed limits (Simpson, 2008;Burritt et al, 1990), leading to a lack of conclusive evidence on the value of school zone signage (Dumbaugh and Frank, 2007;Lee and Bullock, 2003).…”
Section: Driver Speed Compliancementioning
confidence: 96%
“…Based on the results of empirical studies, effective methods include increased enforcement (Dumbaugh and Frank, 2007;Cedar Rapids, 2006), appropriate speed zone settings (Day, 2007;McCoy and Heimann, 1990), visual placement of school buildings and play equipment (Clifton and Kreamer-Fults, 2007), and speed monitoring devices (Ash, 2006;Lee et al, 2006;Cedar Rapids, 2006). Traffic engineers and city planners have utilized a variety of school zone signage in an attempt to improve compliance.…”
Section: Driver Speed Compliancementioning
confidence: 99%
“…Unfortunately, few studies investigate this field of research. One study which investigated engineering countermeasures to enhance traffic safety in school areas is worth mentioning [6], while researchers have also provided new insights, with a focus on safe routes to school, and concluded that further research on the safety of young pedestrians is needed [7]. Information on school-specific traffic situations can be valuable for transportation planners and decision-makers in terms of accident prevention and road engineering.…”
Section: Literature Review 21 School Areasmentioning
confidence: 99%
“…Those that have addressed issues of pedestrian safety have assessed behaviors and perceptions linked to pedestrian safety, rather than crash and injury records (Boarnet et al 2005) or consist of reviews of the existing literature rather than primary data analysis (Dumbaugh and Frank 2007). As part of a series of studies aimed at closing this research gap, we documented the safety benefit and cost-effectiveness of the SRTS program in New York City (DiMaggio and Li 2013; Muennig et al 2014).…”
Section: Introductionmentioning
confidence: 99%